The enterprising admiral : the personal fortune of Admiral Sir Peter Warren - Gwyn, Julian (McGill-Queen's University Press, 1974)
The financial impact of war in the eighteenth century upon the corps of naval officers has not been systematically studied. Nor have the opportunities of a naval career to exploit such sidelines as trade, money-lending, and land purchases in the colonies, where officers spent much of their time, been looked at carefully. The present study analyses in detail the fortune of a single naval officer, Admiral Sir Peter Warren, whose principal wealth came from prize money: the capture of enemy vessels in wartime. He emerges as a new type of entrepreneur, with his feet well planted on both sides of the Atlantic, equally at home in the financial circles of New York, Boston, Charleston, Dublin, and London. Owing to the mobility of his naval career he became familiar with the economic prospects in these scattered places, while he possessed the necessary imagination to take advantage of their commercial opportunities. Mobility also enabled him to select personally the agents who served his varied interests. Neither his widow nor his heirs had the same advantages, nor did they possess the same degree of business sense, with the result that his fortune, invested internationally, was eventually repatriated to England.